Off‐axis symbiosis found: characterization and biogeography of bacterial symbionts of Bathymodiolus mussels from Lost City hydrothermal vents - Eric G. DeChaine; Amanda E. Bates; Timothy M. Shank; Colleen M. Cavanaugh (Environmental Microbiology, 2006)
Summary Organisms at hydrothermal vents inhabit discontinuous chemical ‘islands’ along mid‐ocean ridges, a scenario that may promote genetic divergence among populations. The 2003 discovery of mussels at the Lost City Hydrothermal Field provided a means of evaluating factors that govern the biogeography of symbiotic bacteria in the deep sea. The unusual chemical composition of vent fluids, the remote location, and paucity of characteristic vent macrofauna at the site, raised the question of whether microbial symbioses existed at the extraordinary Lost City. If so, how did symbiotic bacteria therein relate to those hosted by invertebrates at the closest known hydrothermal vents along the Mid‐Atlantic Ridge (MAR)? To answer these questions, we performed microscopic and molecular analyses on the bacteria found within the gill tissue of Bathymodiolus mussels (Mytilidae, Bathymodiolinae) that were discovered at the Lost City. Here we show that Lost City mussels harbour chemoautotrophic and methanotrophic endosymbionts simultaneously. Furthermore, populations of the chemoautotrophic symbionts from the Lost City and two sites along the MAR are genetically distinct from each other, which suggests spatial isolation of bacteria in the deep sea. These findings provide new insights into the processes that drive diversification of bacteria and evolution of symbioses at hydrothermal vents.